Digital Sovereignty and The Right to Data: A Comparative Study Between Indonesia, The European Union, and The United States - Rahayudin, Rahayudin; Naseer, Muchammad; Agustina, Nova; Guterres, Antonio (Politeknik Siber Cerdika Internasional, 2025)
Background: The rapid expansion of the global digital economy has intensified the importance of regulating data governance, particularly in relation to digital sovereignty and the protection of personal data. However, significant differences persist among national legal frameworks, creating regulatory gaps in cross-border data governance and oversight mechanisms. This condition raises critical legal and policy challenges, especially for developing countries such as Indonesia. Objective: This study aims to analyze and compare the principles of digital sovereignty and the right to personal data in Indonesia, the European Union, and the United States, as well as to assess their legal implications for national policy formulation in each jurisdiction. Methods: This research employs a descriptive qualitative approach using a comparative juridical method. A statutory approach is applied to examine relevant laws and regulations, a comparative approach is used to analyze differences in data governance frameworks across jurisdictions, and a conceptual approach is employed to explore theoretical perspectives on digital sovereignty and data rights. Results: The findings indicate that Indonesia emphasizes state control over data and the obligations of electronic system operators, the European Union prioritizes comprehensive protection of data subjects’ rights through the General Data Protection Regulation, while the United States adopts flexible, sectoral regulations oriented toward private sector innovation. These differing paradigms result in variations in oversight effectiveness, levels of data protection, and cross-border data transfer mechanisms. Conclusion: This study highlights the urgency for Indonesia to strengthen regulatory harmonization, enhance institutional oversight capacity, and develop equitable cross-border data transfer mechanisms in order to reinforce digital sovereignty while aligning with international data protection standards.